2012
DOI: 10.1080/15427951.2012.671149
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection for Social Networks Using Graphlets

Abstract: Abstract. Several network models have been proposed to explain the link structure observed in online social networks. This paper addresses the problem of choosing the model that best fits a given real-world network. We implement a model-selection method based on unsupervised learning. An alternating decision tree is trained using synthetic graphs generated according to each of the models under consideration. We use a broad array of features, with the aim of representing different structural aspects of the netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 23 publications
(1 reference statement)
0
79
0
Order By: Relevance
“…In [31], it was shown that the SPA model gave the best fit, in terms of graph structure, for a series of social networks derived from Facebook. In [32], some properties of common neighbors were used to explore the underlying geometry of the SPA model and quantify vertex similarity based on distance in the space.…”
Section: Random Graph Modelsmentioning
confidence: 99%
“…In [31], it was shown that the SPA model gave the best fit, in terms of graph structure, for a series of social networks derived from Facebook. In [32], some properties of common neighbors were used to explore the underlying geometry of the SPA model and quantify vertex similarity based on distance in the space.…”
Section: Random Graph Modelsmentioning
confidence: 99%
“…An eigenvalue histogram is a histogram of the eigenvalues of the normalized Laplacian matrix, which all lie between 0 and 2, with equally spaced bins. These techniques are well established in model selection for various types of biological and social networks [6,14].…”
Section: Model Selectionmentioning
confidence: 99%
“…The set of considered network features is a source of diversity in the existing methods. Although some methods use both local and global network features in model selection [28,13], many existing methods are based on graphlet-counting features [29][30][31]25,26]. Graphlet counting is an inefficient approach, often accelerated by sampling [29] or approximation algorithms [32,29] which result in accuracy drops [28].…”
Section: Related Workmentioning
confidence: 99%
“…[28][29][30][31]). Additionally, the existing methods are sensitive to network perturbations, and their accuracy drops considerably if we inject noise to the network by making random changes in network edges.…”
Section: Introductionmentioning
confidence: 97%